Large-scale calculations of excitation energies in coupled cluster theory: The singlet excited states of benzene - Christiansen, Ove; Koch, Henrik; Halkier, Asger; Jo/rgensen, Poul; Helgaker, Trygve; Sánchez de Merás, Alfredo (The Journal of chemical physics, 1996)
Algorithms for calculating singlet excitation energies in the coupled cluster singles and doubles (CCSD) model are discussed and an implementation of an atomic-integral direct algorithm is presented. Each excitation energy is calculated at a cost comparable to that of the CCSD ground-state energy. Singlet excitation energies are calculated for benzene using up to 432 basis functions. Basis-set effects of the order of 0.2 eV are observed when the basis is increased from augmented polarized valence double-zeta (aug-cc-pVDZ) to augmented polarized valence triple-zeta (aug-cc-pVTZ) quality. The correlation problem is examined by performing calculations in the hierarchy of coupled cluster models CCS, CC2, CCSD, and CC3, as well as by using the CCSDR(3) perturbative triples corrections. The effect of triple excitations are less than 0.2 eV for all excitations except for the 2 1E2g state. The calculated excitation energies are compared with experiment and other theoretical results.